The Influence of Using 'CAPAT'-Based Educational Game Media on Critical Thinking Skills and Learning Interest of Students in Civic Education (PPKN) at Ar-Rohmaniyyah High School - Hosen, Hosen; Muhajir, Muhajir; Wahid, A. (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The purpose of this study is to find out: (1) The effect of the use of educational game-based learning media